Understanding Global Skills for 21st Century Professions - Bourn, Douglas (Springer International Publishing, 2018)
This book highlights the increasing need for people who will be working in professions such as teaching, health, engineering and business management to have the skills for living and working in a global society. Globalisation and the challenges resulting from recent political events in Europe and North America have given rise to a need for training and further and higher education programmes to address the skills young people all need to effectively engage in the current global society. Reviewing the range of theories and debates surrounding skills for the twenty-first century, the author suggests there is a need to directly address the real-world issues of today and move beyond abstract concepts such as team work, critical thinking and problem solving, as important as these concepts are. The author proposes a new framework for global skills using examples from international and national policy-makers and evidence from further and higher educational programmes and training courses. This pioneering yet practical book will be of value to students and scholars of global education as well as practitioners and policy makers.